If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -5) + x = 6(7 + -1x) Reorder the terms: 6(-5 + x) + x = 6(7 + -1x) (-5 * 6 + x * 6) + x = 6(7 + -1x) (-30 + 6x) + x = 6(7 + -1x) Combine like terms: 6x + x = 7x -30 + 7x = 6(7 + -1x) -30 + 7x = (7 * 6 + -1x * 6) -30 + 7x = (42 + -6x) Solving -30 + 7x = 42 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -30 + 7x + 6x = 42 + -6x + 6x Combine like terms: 7x + 6x = 13x -30 + 13x = 42 + -6x + 6x Combine like terms: -6x + 6x = 0 -30 + 13x = 42 + 0 -30 + 13x = 42 Add '30' to each side of the equation. -30 + 30 + 13x = 42 + 30 Combine like terms: -30 + 30 = 0 0 + 13x = 42 + 30 13x = 42 + 30 Combine like terms: 42 + 30 = 72 13x = 72 Divide each side by '13'. x = 5.538461538 Simplifying x = 5.538461538
| (2x^2+35)=(1315-3x^2) | | 5.5+-x=-4.5+-x | | 5(f-91)-87=-52 | | 7=x-(-14) | | 8y-28=6y+3 | | 2b/4=-18-9b | | 1/5y-1=-6 | | x+8-5x+3=4x+3x-8+16 | | 4x+6=3x-36 | | 4g+3(-3+4g)=1-g | | 8(y-8)/3 | | c=48y | | 250+12x=475 | | 2h-7=-9h-26 | | 5(f-91)-87=52 | | 5y=-50-x | | -3(-4x+5)=5(-3x+7)+10 | | 6(x-5)+6=6(7-x) | | -2x-8=x+4 | | -0.66w=60 | | 4x+8-2x=6x-4 | | -3x+7y-7=-12-8y | | 6n+9=2n-23 | | 400mg=Xkg | | 11m+2=53 | | 8/12=r/r | | 4/3u-2/3=-6/1u-5/4 | | 0.05w=6.2 | | 4x^3+4x^2-8x+8=0 | | (9/y)+(2/3)=(9/3y) | | 4+x/3=-4 | | H-6+7h= |